Земпер - Имидокислоты (1991)
Вых. дан. ориг.: СПб.: Типо-литогр. И. А. Ефрона, 1894 Экземпляры: СБО (20110624) / Инвентарный номер: 1009738 / Цена: 1000.00 / Сис.шифр: 92 / Авт.знак: Э 68 / ГРНТИ: 00 / ББК: 92.0